The effect of different light-curing units on tensile strength and microhardness of a composite resin - Franco, Eduardo Batista [UNESP]; Dos Santos, Patrícia Aleixo [UNESP]; Mondelli, Rafael Francisco Lia [UNESP] (FapUNIFESP (SciELO), 2007)
The aim of this study was to evaluate the influence of different light-curing units on the tensile bond strength and microhardness of a composite resin (Filtek Z250 - 3M/ESPE). Conventional halogen (Curing Light 2500 - 3M/ESPE; CL) and two blue light emitting diode curing units (Ultraled - Dabi/Atlante; UL; Ultrablue IS - DMC; UB3 and UB6) were selected for this study. Different light intensities (670, 130, 300, and 600 mW/cm2, respectively) and different curing times (20s, 40s and 60s) were evaluated. Knoop microhardness test was performed in the area corresponding to the fractured region of the specimen. A total of 12 groups (n=10) were established and the specimens were prepared using a stainless steel mold composed by two similar parts that contained a cone-shaped hole with two diameters (8.0 mm and 5.0 mm) and thickness of 1.0 mm. Next, the specimens were loaded in tensile strength until fracture in a universal testing machine at a crosshead speed of 0.5 mm/min and a 50 kg load cell. For the microhardness test, the same matrix was used to fabricate the specimens (12 groups; n=5). Microhardness was determined on the surfaces that were not exposed to the light source, using a Shimadzu HMV-2 Microhardness Tester at a static load of 50 g for 30 seconds. Data were analyzed statistically by two-way ANOVA and Tukey's test (p<0.05). Regarding the individual performance of the light-curing units, there was similarity in tensile strength with 20-s and 40-s exposure times and higher tensile strength when a 60-s light-activation time was used. Regarding microhardness, the halogen lamp had higher results when compared to the LED units. For all light-curing units, the variation of light-exposure time did not affect composite microhardness. However, lower irradiances needed longer light-activation times to produce similar effect as that obtained with high-irradiance light-curing sources.
Keywords: LED; Microhardness; Photopolymerization; Tensile strength